2015
DOI: 10.18632/oncotarget.5682
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble programmed death ligand 1 predict treatment response and progression free survival in multiple myeloma

Abstract: Immune checkpoint signaling plays an important role in immunosuppression in multiple myeloma (MM). Blood levels of soluble programmed death-ligand 1 (sPD-L1), a checkpoint-relevant protein, might predict treatment response and survival outcomes in MM patients. We used an enzyme-linked immunosorbent assay to measure serum sPD-L1 levels in 81 newly diagnosed MM patients. We found that myeloma patients had higher sPD-L1 concentrations than healthy controls. The best sPD-L1 cutoff value for predicting disease prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(153 citation statements)
references
References 34 publications
8
141
4
Order By: Relevance
“…54 Using this approach, researchers were able to demonstrate that sPD-L1 is a good prognostic marker in multiple myeloma and DLBCL. 55,56 In a small study with 81 multiple myeloma patients, the mean concentration of sPD-L1 was 2.851 ng/mL compared with 0.716 ng/mL sPD-L1 in matched controls. 55 Additionally, a lower sPD-L1 in patients with multiple myeloma is associated with higher progression-free survival.…”
Section: Strategies To Measure Pd-l1/pd-1 Expression Immunohistochemimentioning
confidence: 98%
“…54 Using this approach, researchers were able to demonstrate that sPD-L1 is a good prognostic marker in multiple myeloma and DLBCL. 55,56 In a small study with 81 multiple myeloma patients, the mean concentration of sPD-L1 was 2.851 ng/mL compared with 0.716 ng/mL sPD-L1 in matched controls. 55 Additionally, a lower sPD-L1 in patients with multiple myeloma is associated with higher progression-free survival.…”
Section: Strategies To Measure Pd-l1/pd-1 Expression Immunohistochemimentioning
confidence: 98%
“…In other cancer entities, different approaches to determine prognostic cut-off values have been used: median sPD-L1 serum level in the analyzed cancer patient cohort, sPD-L1 serum levels in a corresponding cohort of healthy individuals or receiver operating characteristic (ROC) curve models to define an ideal prognostic cut-off value. [14][15][16][17][18] In all aforementioned studies, the prognostic cut-off value was in the range of the 50th (i.e., median) and 75th percentile of the observed sPD-L1 levels in the whole analyzed patient cohort. When designing our study we therefore decided to use the median and the 75th percentile of sPD-1 and sPD-L1 levels observed in our study to define a cohort of patients with high versus low levels of the two molecules.…”
Section: Spd-1 and Spd-l1 Elisasmentioning
confidence: 99%
“…As the use of these agents expands, and a variety of other immunotherapy agents are developed (12), significant value has been shown in predicting which patients will respond to PD-1 pathway blockade, in contrast to other patients for whom other agents or combination treatment strategies may be more appropriate. Mutational or neoantigen load, PD-ligand 1 (PD-L1) expression, and defects in mismatch repair have all been proposed as potential predictors of treatment response to PD-1 inhibition (4,(13)(14)(15)(16)(17)(18)(19). Data have also indicated that patients with CD8 þ T-cell infiltrate within or in proximity to the tumor microenvironment may preferentially respond to immunotherapies (18,20,21).…”
Section: Introductionmentioning
confidence: 99%